Kidney transplantation from a mother with unrecognized Fabry disease to her son with low α‐galactosidase A activity: A 14‐year follow‐up without enzyme replacement therapy. (July 2016) - Odani, Keiko; Okumi, Masayoshi; Honda, Kazuho; Ishida, Hideki; Tanabe, Kazunari
Abstract: We report a case of kidney transplantation from mother to son, both of whom were likely to have had an unrecognized renal variant phenotype of Fabry disease. The patient was a 54‐year‐old man, with an unknown primary cause of end stage renal disease. He had no notable past medical history, other than end stage renal disease. He underwent living‐related kidney transplantation from his mother at age 40 years. Foam cells in the glomeruli were identified on histology assessment of a 0‐hour allograft biopsy, with zebra bodies identified in the glomerular visceral epithelial cells by electron microscopy. These findings were indicative of Fabry disease in the donated kidney. As a definitive diagnosis of Fabry's disease could not be confirmed, enzyme replacement therapy was not initiated. Thirteen years after kidney transplantation, the patient underwent left nephrectomy for a left renal tumour, with pathological findings of clear cell carcinoma, foam cells and zebra bodies in the native kidney. Detailed examinations identified low α‐galactosidase A activity and mutation of the α‐Gal A gene, confirming a diagnosis of a renal variant phenotype of Fabry disease. Histology of several allograft biopsies performed over the 14 years from the time of kidney transplantation revealed only moderate interstitial fibrosis and tubular atrophy, with no evidence of disease progression on electron microscopy, despite the presence of zebra bodies in the glomerular visceral epithelial cells.